Arsenic mitigation in rice grain loading via alternative irrigation by proposed water management practices. (January 2020) - Shrivastava, Anamika; Barla, Anil; Majumdar, Arnab; Singh, Surjit; Bose, Sutapa
Abstract: Over the past three decades, the occurrence of high concentrations of arsenic (As) in drinking-water and its subsequent poisoning in rice has been recognized as a major public-health concern globally, especially in Ganga Delta Plain with more than 80 million peoples in serious As exposure far beyond than its allowable limit. An extensive field study was conducted for consecutive four years viz. 2013 to 2016, introducing a process of intermittent irrigation pattern comparing to the conventional practice of rice cultivation in India. The practice provides a combination of aerobic and anaerobic irrigation resulting better rice productivity with lesser arsenic mobility and accumulation in rice grains. This present research finding clearly points out to the marked reduction of arsenic load from average 1.6 mg/kg to 0.5 mg/kg in rice grain, much closer to FAO/WHO prescribed safe limit and in the continuous practice of proposed agricultural strategy resulting in a gradual decrease of 15% bioavailable arsenic in each year. Total productivity (in kg/hectare) also increased by 540 kg/year in boro and 340 kg/year in amon subsequently achieving the prescribed safe limit of As in grain. Graphical abstract: Image 1 Highlights: Continuously flooded field releases higher amount of arsenic into aqueous phase. Arsenic accumulation in rice grain creates potential ecological and health risks. Introducing intermittent irrigation practice reducing arsenic bioavailability. Intermittent irrigation reduces arsenic loading in rice grain increasing yield. Intermittent practice is proved to be better than both aerobic and anaerobic practices.